2017
DOI: 10.1038/srep45010
|View full text |Cite
|
Sign up to set email alerts
|

Scleraxis is required for maturation of tissue domains for proper integration of the musculoskeletal system

Abstract: Scleraxis (Scx) is a basic helix-loop-helix transcription factor that is expressed persistently in tendons/ligaments, but transiently in entheseal cartilage. In this study, we generated a novel ScxCre knock-in (KI) allele, by in-frame replacement of most of Scx exon 1 with Cre recombinase (Cre), to drive Cre expression using Scx promoter and to inactivate the endogenous Scx. Reflecting the intensity and duration of endogenous expression, Cre-mediated excision occurs in tendinous and ligamentous tissues persist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
104
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 89 publications
(111 citation statements)
references
References 42 publications
6
104
1
Order By: Relevance
“…Tnmd expression was observed by us, along with other researchers, in tendons, ligaments, eyes, and CTC (Brandau et al, ; Kimura et al, ; Shukunami et al, ). In the vertebral column, previous studies have localized Tnmd gene expression to areas of the IVD (Minogue et al, ; Nakamichi et al, ), as well as Tnmd immunostainings carried out in neonate mice detected robust protein expression in the OAF (Yoshimoto et al, ). To further determine the precise distribution of Tnmd in the postnatal and adult IVD, we first performed immunolocalization studies on IVD tissues from WT mice at distinct stages of skeletal development ranging from newborn to 18 months of age.…”
Section: Resultsmentioning
confidence: 97%
“…Tnmd expression was observed by us, along with other researchers, in tendons, ligaments, eyes, and CTC (Brandau et al, ; Kimura et al, ; Shukunami et al, ). In the vertebral column, previous studies have localized Tnmd gene expression to areas of the IVD (Minogue et al, ; Nakamichi et al, ), as well as Tnmd immunostainings carried out in neonate mice detected robust protein expression in the OAF (Yoshimoto et al, ). To further determine the precise distribution of Tnmd in the postnatal and adult IVD, we first performed immunolocalization studies on IVD tissues from WT mice at distinct stages of skeletal development ranging from newborn to 18 months of age.…”
Section: Resultsmentioning
confidence: 97%
“…; Yoshimoto et al. ) and is involved in regulating Tnmd expression, which itself serves as tendon and tendon progenitor cell marker (Shukunami et al. ).…”
Section: Resultsmentioning
confidence: 99%
“…Scleraxis appears to be important in embryonic tendon development, in part, by directing the expression of type I collagen, tenomodulin, and fibronectin (12,13,(31)(32)(33). Mechanical loading increases the expression of scleraxis, type I and III collagen, and tenomodulin in tendon (6,14,34,35), and our transcriptomic analyses demonstrated that expression of components or regulators of the ECM, including Col1a1, Mkx and Tnmd, were found to be reduced in the absence of scleraxis in whole tendons and in cultured tenocytes.…”
Section: Discussionmentioning
confidence: 53%